Urban rural relations and regional development - "Kaur, Ravinder" (New Delhi, 2007)
Urban rural relations have been conceptualised and interpreted in terms of diverse processes like separation, polarisation, opposition, domination/subordination and more recently nexus formation. Infact urban rural relations have always been interdependent even through the intensity, nature, extent and direction of these relations have been varying in time and space.
Keywords: Rural relation